KONSEP KURIKULUM MUATAN LOKAL KEAGAMAAN SOLUSI PENINGKATAN PEMAHAMAN AGAMA ISLAM - Indana, Nurul; Indah Nur Sholichah, Yekti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This local Islamic religious content is an evolution of the learning system that is generally implemented in all Tsanawiyah madrasas, because from the start it was implemented in a special way. To maintain the madrasah tradition in maintaining the mastery paradigm of